Kirjanpitotilojen tuloksia: alustavia tietoja tilivuodelta 1997 - Riepponen, Leena (Maatalouden taloudellinen tutkimuslaitos, 1998)
This paper presents a brief account of the preliminary results of the profitability study concerning the Finnish agriculture in 1997. The number of farms included in the study is 530, which is about half of the bookkeeping farms in Finland. Only the main points in the results for 1997 are compared with those of previous year. The results are presented as averages for all farms as well as grouped according to the size and type of farms. The results for the different production lines are also presented according to the support areas. The year 1997 was the third year of Finland in the EU. According to the preliminary bookkeeping data for 1997, the average farm income per hectare was FIM 3,414, which is 14% smaller than before the EU membership in 1994. According to the production lines, there was some improvement in the farm income per hectare from 1996 on cattle and pig farms, but on crop producing farms the farm income was slightly lower than in 1996.
Preliminary results of bookkeeping farms in 1997
Keywords: Ma; kirjanpitotilat; tulot; kannattavuus; hinnat; accounting; bookkeeping; farm results; income; profitability; costs